Gaya hidup terkait hipertensi pada pasien di Puskesmas Batoh, Kota Banda Aceh - Raisha Armaliza Bahar; Fachmi Ichwansyah; Asnawi Abdullah (Poltekkes Kemenkes Aceh, 2025)
Background: The mortality rate caused by hypertension is still high in Indonesia. One of the important factors that influence the occurrence of hypertension complications lifestyle. An unhealthy lifestyle can trigger an increase in blood pressure or hypertension.Objective: The purpose of this study was to determine the lifestyle of patients diagnosed with hypertension at the Banda Aceh City Health Center, Banda Aceh City in 2019.Methods: This research is quantitative with a cross sectional design. Data collection was done by interview using a questionnaire. Samples were taken by accidental sampling technique, 47 samples were obtained, data collection was carried out from August to September 2019. Univariate analysis was carried out by descriptive analysis, bivariate analysis was carried out by calculating the Odd Ratio (OR) value calculated using conditional logistic regression using the logit procedure of the STATA 14,0 program, and multivariate analysis was carried out by correlating several independent variables with one dependent variable simultaneously with the results of bivariate test significant value (p ≤ 0,05) with 95% CI.Results: The results of the study statistically showed There is no significant relationship between patients diagnosed with hypertension and stress management factors (p value 0,65), and smoking history factors (p value 0,47), while there is a significant relationship between patients diagnosed with hypertension and food consumption (p value 0,00), and physical activity (p value 0,00).Conclusion: Patients who have been diagnosed with hypertension, to be required to undergo routine lifelong treatment and maintain a healthy lifestyle so that hypertension can be controlled and does not cause complications.